Respuestas
Respuesta dada por:
1
Respuesta:
a) X – 5 + X - 2 = X + 3
x + x - x = 3 + 5 + 2
x = 10
b) 4(X – 10) = –6(2 – X) – 5X
4 ( x – 10 ) = – 6 (2 – x) – 5x
4x - 40 = - 12 + 6x - 5x
4x - 6x + 5x = - 12 + 40
3x = 28
x = 28 / 3
Espero que te sirva!!✔❤
Respuesta dada por:
1
Respuesta:
A) RTA: X=318136
Explicación paso a paso:
-5+X-2=318129
-7+X=318129
X=318129+7
X=318136
B) RTA: X=28/3
Explicación paso a paso:
4X-40=-12+6X-5X
4X-X=-12+40
3X=28
X=28/3
Preguntas similares
hace 3 años
hace 6 años
hace 8 años
hace 8 años
hace 8 años